2012
DOI: 10.5402/2012/837270
|View full text |Cite
|
Sign up to set email alerts
|

The Prevalence of Dental Anomalies in the Western Region of Saudi Arabia

Abstract: Objective. The aim of this cross-sectional study was to investigate the prevalence of dental anomalies that could be a cause of malocclusion in the western region of Saudi Arabia. Materials and Methods. A retrospective study of 878 digital orthopantomograms (OPGs) taken of patients, age ranging between 12 and 30 years, who presented to treatment at the Faculty of Dentistry, King Abdulaziz University, Jeddah, Saudi Arabia between 2002 and 2011. The OPGs and dental records were reviewed for congenitally missing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

26
142
13
15

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 107 publications
(196 citation statements)
references
References 21 publications
(28 reference statements)
26
142
13
15
Order By: Relevance
“…This study found a significant prevalence of developmental dental anomalies in Brazilian orthodontic patients, with high prevalence in females, similar to the results found by other authors (5,6,13,19). Hypodontia was observed significantly more in women; other authors have also reported prevalence of microdontia in females, while hyperdontia and macrodontia were more frequent in males (13).…”
Section: Discussionsupporting
confidence: 80%
See 3 more Smart Citations
“…This study found a significant prevalence of developmental dental anomalies in Brazilian orthodontic patients, with high prevalence in females, similar to the results found by other authors (5,6,13,19). Hypodontia was observed significantly more in women; other authors have also reported prevalence of microdontia in females, while hyperdontia and macrodontia were more frequent in males (13).…”
Section: Discussionsupporting
confidence: 80%
“…The patients' age ranged from 7-42 years old, with most of the dental anomalies diagnosed between 11 and 20 years, and this result was similar to that found in the literature (5,13,19). The time of tooth formation may interfere with the diagnosis of each anomaly.…”
Section: Discussionsupporting
confidence: 76%
See 2 more Smart Citations
“…7 These anomalies may involve or arise in a single tooth or may be a part of systemic disorder or a syndrome that arise generalized to involve all the teeth. 8 Review of the literature has shown varying data on the prevalence of these DAs. The discrepancies in the data may be attributed to racial differences, different sampling techniques, and different diagnostic criteria.…”
Section: Introductionmentioning
confidence: 99%